Anti-atherosclerotic effects and molecular targets of salvianolic acids from Salvia miltiorrhiza Bunge - Liang, Qingzhi; Liu, Xiaoqin; Xu, Xin; Chen, Zhengtao; Luo, Ting; Su, Yi; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2025)
Salvia miltiorrhiza Bunge [Lamiaceae; Salviae miltiorrhizae radix et rhizoma] is a traditional Chinese medication used extensively as a therapeutic agent against atherosclerosis (AS) because of its substantial cardiovascular protective properties as well as ability to regulate the signaling cascades and molecular targets involved in AS. Preclinical research has shown that the hydrophilic metabolites of S. miltiorrhiza Bunge represented by danshensu (DSS), salvianolic acid A (SAA), and salvianolic acid B (SAB) can reduce endothelial dysfunction, inhibit smooth muscle cell migration and proliferation, block platelet aggregation, have antithrombotic properties, and modulate vascular tone. Furthermore, studies have shown that salvianolic acid is clinically beneficial, while some evidence also supports its safety and effectiveness in diseases linked to AS. The present study is a review of the anti-atherosclerotic pharmacological activities, pharmacokinetic characteristics, drug interactions, and safety evaluations of salvianolic acid over the last 20 years. Herein, we focus on the cellular targets linked to AS; clarify the molecular mechanisms of the anti-atherosclerotic activities of DSS, SAA, and SAB; and discuss the future needs and priorities in light of the limitations of the existing studies. This review is intended to establish the groundwork and offer a thorough perspective for deeper investigations of the studies, clinical uses, and product development efforts of salvianolic acid as a natural modulator of AS.